Recent changes (2013-2017) in scyphomedusan fauna in the Boka Kotorska Bay, Montenegro (Southeast Adriatic) - Violić, Ivana; Kogovšek, Tjaša; Pestorić, Branka; Mačić, Vesna; Milić Beran, Ivona; Lučić, Davor (2019)
A semi- quantitative time series (2013-2017) was used to present the recent events of scyphomedusae appearance and abundance in the Boka Kotorska Bay, Montenegro, Southeast Adriatic. Six meroplanktonic species were recorded: Aurelia spp, Chrysaora hysoscella, Cotylorhiza tuberculata ̧ Discomedusa lobata, Drymonema dalmatinum and Rhizostoma pulmo. Among them, C. hysoscella and D. lobata dominated in the water column during winter and spring, forming dense aggregations in March and May, and February to May, respectively. Our description of the D. lobata blooms are actually the first known records of blooms for this species. C. tuberculata was observed in the Bay principally in August and September. The bloom was occurred only in 2017, being the first information of C. tuberculata mass appearance in this area. We hypothesized that global warming phenomena could trigger the observed changes, and in this respect, long-term trends of sea surface temperature (SST) fluctuations were analysed. The scyphomedusae blooms coincided with high positive SST anomalies, noted in the last seven years for this area. To better understand the mechanisms underlying changes in their phenology and abundance, detailed studies on benthic stages in the Bay are essential.
Semi kvantitativne serije podataka (2013.-2017.) upotrjebljene su za prikaz novonastalih promje-na pojave i brojnosti režnjaka u akvatoriju Bokokotorskog zaljeva. Pretpostavljajući da bi globalno zagrijavanje moglo potaknuti promatrane promjene, analizirani su dugoročni trendovi fluktuacija površinske temperature mora. Zabilježeno je šest meroplanktonskih vrsta: Aurelia spp, Chrysaora hysoscella, Cothyloriza tuberculata ̧ Discomedusa lobata, Drymonema dalmatinum i Rhizostomapulmo. Među njima C. hysoscella, i D. lobata su bile veoma česte i brojne., formirajući nakupine velikih gustoća tijekom zime i proljeća. Za vrstu D. lobata je ujedno prvi poznati opis masovne pojave ove meduze. Vrsta C. tuberculata je u akvatoriju bila primijećena tijekom ljeta, a u velikim gustoćama samo u 2017. godini. To je prvi dokumentirani opis masovne pojave ove meduze u Boko-kotorskom zaljevu. Pojave mase režnjaka u plankton podudaraju se s visokim odstupanjima površin-ske temperature mora zabilježenih posljednjih sedam godina. Stoga, naši opisi fenologije i brojnosti režnjaka u Bokokotorskom zaljevu su u skladu s dokazima porasta gustoće populacija želatinoznog zooplanktona na globalnoj skali. Za bolje razumijevanje mehanizma opisanih promjena neophodno je provesti detaljna istraživanja biologije i ekologije bentonskih stadija ovih organizama.
Bibliografija: str. 35-38.
Summary ; Sažetak.
Keywords: Režnjaci -- Zooplankton -- Želatinozni zooplankton -- Fenologija -- Temperatura mora; Sredozemno more -- Bokokotorski zaljev -- Crna Gora